2018
DOI: 10.1007/s40037-018-0429-6
|View full text |Cite
|
Sign up to set email alerts
|

Shame

Abstract: None

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 7 publications
(5 reference statements)
0
10
0
Order By: Relevance
“…Importantly, there is no evidence that our approach caused significant emotional distress in student participants, as has been reported by others. 5 Numerous aspects of our seminar seemed to enable its positive outcomes and avoid learner distress. First, we used personal narrative to develop an emotional connection to the topic, model vulnerability, and establish an environment of psychological safety for subsequent small-group discussions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Importantly, there is no evidence that our approach caused significant emotional distress in student participants, as has been reported by others. 5 Numerous aspects of our seminar seemed to enable its positive outcomes and avoid learner distress. First, we used personal narrative to develop an emotional connection to the topic, model vulnerability, and establish an environment of psychological safety for subsequent small-group discussions.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4] Few published strategies have focused on promoting emotional resilience in learners, and only one published innovation has directly addressed shame in medical students. 5 Notably, the authors of this paper reported inadvertently inducing shame in participating students, a workshop outcome that highlights the challenge of directly addressing this oft-stigmatized topic. 5 Shame is a normal, negative self-conscious emotion that occurs when an individual engages in a self-evaluation and attributes a triggering event (e.g., a medical error, test failure) to a global deficiency of the self.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…I decided to explore whether relevant literature describing failed scholarly projects in HPE could be captured by the taxonomy in order to explore the applicability of this taxonomy to published works. I chose to draw on all papers published to date in the Perspectives on Medical Education 'failures/surprises' series [22,[24][25][26][27][28][29][30][31][32][33][34][35][36], as these publications were identified by their authors to be a direct result of a failed scholarly project or innovation [22,[25][26][27][28][29][30][31][32][33][34][35][36]. I then categorized the publications (n = 13), and have included them throughout as examples of the proposed taxonomy, with a summary available in Tab.…”
Section: Generation Of the Taxonomy Of Forms Of Failurementioning
confidence: 99%
“…This serendipitous failure may be one of more common types of failure in research and scholarship-the occurrence of the un-expected, and the careful investigation that follows. Drawing on publications of failed scholarly projects, serendipitous failure can result in a challenge to our understanding of a given research domain [22] or educational learning objective [33], of our research [34] or educational practice [35,36]. This opportunistic failure focuses on engaging with and chasing the unexpected finding to try to understand the 'why' behind the pattern of findings [42].…”
Section: Serendipitous Failurementioning
confidence: 99%